Pengaruh Kualitas Buah yang Diolah terhadap Daya Serap Janjang Kosong dengan Variabel Berondolan - Azhar Basyir Rantawi (JURNAL CITRA WIDYA EDUKASI, 2017)
The oil losses that occurs in the processing of FFB is inevitable, but can be controlled in such a way that it can be minimized in accordance with predetermined standard. Parameters of oil losses that must be controlled, one of which is the oil content absorbed in empty bunch. The level of oil losses in this empty bunch often exceed the standard limit. If this happens, it will affect the performance of oil extraction rate expected by the palm oil mill. The FFB received at the palm oil mill consists of five grades and to differentiate it will be done grading process. Sampling consisting of 1 kg of fruit bunch and 3 kgs of loss fruit, consisting of normal and damaged of loss fruit, done after the grading process is completed. Sterilizing the sample will be done after all samples collected. Sterilizng is done inside the sterilizer and all samples are sterilized on the same sterilizer. Samples that have been sterilized will be analyzed oil content in empty bunch. The result showed that the quality of processed FFB greatly affects the percentage rate of oil losses in empty bunch. Based on the result of the analysis it can be concluded that the higher the FFB is damaged then the percentage level of oil losses in empty bunch will be higher also. Similarly, the leftover fruit bunch will experience the same thing as well.